2020
DOI: 10.3389/fneur.2020.00439
|View full text |Cite
|
Sign up to set email alerts
|

Novel in vivo Assessment of Unruptured Intracranial Aneurysm Inflammatory Factors

Abstract: Background and Purpose: The growth and eventual rupture of intracranial aneurysms may be due to an underlying inflammatory process as evidenced by pathological examination of aneurysm walls. We hypothesize that unruptured aneurysms have an increased inflammatory milieu within their lumen in comparison to the rest of the cerebral arterial vascular system. Methods: Blood was sampled from unruptured aneurysms in patients presenting for aneurysm coil embolization and C3 and C4 complement values from this serum wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…In our series, we observed that positive effects for CD68, in line with previous literature reports ( 27 29 ), were associated with a high percentage of SAH. These patients exhibited an increase in ECM along with rarefaction of the muscular component through the aneurysm wall.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our series, we observed that positive effects for CD68, in line with previous literature reports ( 27 29 ), were associated with a high percentage of SAH. These patients exhibited an increase in ECM along with rarefaction of the muscular component through the aneurysm wall.…”
Section: Discussionsupporting
confidence: 93%
“…CD68 and GFAP ( 25 ) are highly correlated with circulating macrophages, which are typically involved in the inflammatory mechanisms of IA. In recent times, it has been highlighted by various authors ( 19 23 , 26 , 27 ) that the percentage of CD68-positive cells in recently ruptured aneurysm domes (within 2 days) is significantly higher compared with the percentage in unruptured aneurysm domes. The presence of foaming elements of macrophagic nature (foam cells) indicates a high concentration of lipid material, similar to that seen in vessels with atherosclerotic plaques, along with an inflammatory process in the aneurysm wall.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, it remains elusive whether intracranial aneurysm rupture (as a local event with an immediate systemic inflammatory increase) or the preexisting condition of chronic inflammation is causative of higher suPAR levels. However, it is conceivable that a local, compartmentalized inflammatory processes within the cerebral aneurysm wall are probably not detectable systemically, rendering an early inflammatory response caused by the rupture more likely ( 47 ). An alternative hypothesis may be that chronic, low grade, but systemic inflammation may support or even initialized the formation of aneurysm ( 48 ).…”
Section: Discussionmentioning
confidence: 99%